Kapasitas Pendamping Desa Dalam Implementasi UU Desa Di Jawa TengaH 2018 - Suharto, Suharto (LP2M, 2020)
Abstract Village Facilitation Capacity is the ability to carry out activities / actions for community empowerment through assistance, organization, direction and facilitation of the Village. Village facilitation in the framework of implementing Law Number 6 of 2014 concerning Villages is very important in determining its success. Seeing the current condition of the village which is very heterogeneous in terms of quantity, quality or capacity and even the potential of natural resources and human resources is very varied, the role of village assistance in the framework of implementing the Village Law is very important in helping villages implement the mandate of the Village Law. The Village Facilitator is assigned to assist the Village in organizing Village development and empowering the Village community in Central Java. In terms of quantity, most villages currently do not have complete equipment as regulated in PP 43/2014 article 61-article 64. Meanwhile, the available capacity of the equipment still needs to be improved. Second, the quality of the preparation of the Village Development Planning document (RPJM Desa, RKP Desadan APB Desa). Based on PP 43/2014 articles 114-115 and PP 60/2014 article 20 it is mentioned that the use of Village Funds refers to the Village Medium Term Development Plan (RPJMDes) and the Village Government Work Plan (RKPDes). Village Facilitators carry out the task of assisting Villages in the implementation of the Village Law in Central Java which includes, among others: a. assist the Village in planning, implementing, and monitoring Village development and empowering the Village community; b. assist the Village in carrying out management of basic social services, the development of the Village economic effort, the utilization of natural resources and appropriate technology, the construction of Village infrastructure, and the empowerment of the Village community; c. conduct capacity building for the Village Government, Village community organizations. The implementation of the Village Law is not only determined by the Village Facilitators, but also by the Village Government who has mastered the technical and financial management mechanisms that are trained, professionally and mastered in assisting village community empowerment programs assisted and facilitated by community facilitators. Keywords: Village Facilitator Capacity, Implementation, Village Law.